2013
DOI: 10.1242/dev.095513
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant H3.3 maintains a decondensed chromatin state essential for mouse preimplantation development

Abstract: Histone variants can replace canonical histones in the nucleosome and modify chromatin structure and gene expression. The histone variant H3.3 preferentially associates with active chromatin and has been implicated in the regulation of a diverse range of developmental processes. However, the mechanisms by which H3.3 may regulate gene activity are unclear and gene duplication has hampered an analysis of H3.3 function in mouse. Here, we report that the specific knockdown of H3.3 in fertilized mouse zygotes leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 49 publications
9
133
0
Order By: Relevance
“…We found that injection of K4M mutants before fertilization, but not after fertilization, significantly decreased the embryo survival rate (Fig 1B and C), suggesting that although the retarded cell growth in K4M-injected embryos occurred after the 8-cell stage, the cause of the abnormality had already occurred in the zygotic stages. Other than the K4M mutant, the K36M mutant also exhibited significant growth retardation when it was injected before fertilization ( Supplementary Fig S2A), consistent with previous work demonstrating the importance of H3.3 K36 methylation for early embryonic development [9]. In contrast, K9M and K27M mutants did not exhibit any significant abnormalities ( Supplementary Fig S2B and C), which conflicts with a previous study demonstrating developmental alteration by H3.3 K27R-EGFP mRNA [6].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We found that injection of K4M mutants before fertilization, but not after fertilization, significantly decreased the embryo survival rate (Fig 1B and C), suggesting that although the retarded cell growth in K4M-injected embryos occurred after the 8-cell stage, the cause of the abnormality had already occurred in the zygotic stages. Other than the K4M mutant, the K36M mutant also exhibited significant growth retardation when it was injected before fertilization ( Supplementary Fig S2A), consistent with previous work demonstrating the importance of H3.3 K36 methylation for early embryonic development [9]. In contrast, K9M and K27M mutants did not exhibit any significant abnormalities ( Supplementary Fig S2B and C), which conflicts with a previous study demonstrating developmental alteration by H3.3 K27R-EGFP mRNA [6].…”
Section: Resultssupporting
confidence: 82%
“…Particularly, histone H3.3, one of the histone variants that is incorporated into chromatin independently of DNA replication, is predominantly incorporated into the paternal PN soon after fertilization [5,8]. The impairment of K27 methylation and K36 methylation of H3.3 by using their lysine-arginine substituted mutants (i.e., H3.3-K27R and H3.3-K36R, respectively) has been reported to critically affect the development of preimplantation embryos; these effects were not observed when H3.1 was used [6,9]. Collectively, these findings demonstrate the critical role of histone methylation in embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…In mouse ESCs, H3.3 is required for proper establishment of H3K27me3 at the promoters of developmentally regulated genes. It is also thought to be responsible for the chromatin conformation changes during embryo development, as well as for the establishment/maintenance of PTMs involved in the regulation of developmental genes [33,34,36]. These and other studies showed that H3.3 is an essential component of development and important for establishing chromatin structures and epigenetic states in this process [37,38].…”
Section: H33's Roles In Epigenome Reprogramming and Embryonic Develomentioning
confidence: 82%
“…Mice that harbor targeted disruption of the H3f3b gene not only have disrupted expression of spermatogenesis-related genes, but also have defects in the histone-to-protamine replacement during spermatogenesis [35]. H3.3 also has a role in maintaining proper chromatin structure during the initial stages of embryonic development, and loss of H3.3 often leads to missegregation of chromosomes [33,34]. In mouse ESCs, H3.3 is required for proper establishment of H3K27me3 at the promoters of developmentally regulated genes.…”
Section: H33's Roles In Epigenome Reprogramming and Embryonic Develomentioning
confidence: 99%
“…The function of H3.3 in early embryo development H3.3 takes part in various stages of development, such as gametogenesis, fertilization and differentiation (Bush et al, 2013;Lin et al, 2013;Tang et al, 2015;Wen et al, 2014a;Yuen et al, 2014) (Figure 2A). Knockout animal models for H3.3 or H3.3-specific chaperones have revealed the essential functions of H3.3 during development (Garrick et al, 2006;Michaelson et al, 1999;Roberts et al, 2002;Tang et al, 2015).…”
Section: The Functions Of H33 In Developmentmentioning
confidence: 99%